К этимологии осетинского ziw | zew - Дзиццойты, Ю. А. (ИАЭ)
В статье рассматривается терминология института трудовой взаимопомощи у осетин, известного также и у многих других народов. Один из видов этого описанного в этнографической литературе феномена до сих пор не имел этимологии на осетинском материале. В настоящей статье предлагается описание и этимология одного из актуальных в данном комплексе терминов – ziw | zew. The article discusses the terminology of the tradition of cooperative work among Ossetians, known among rural communities worldwide. One term of this tradition, described in ethnographic literature, until now has had no etymology in the Ossetian language. We propose a description of one of the relevant terms of this tradition – ziw | zew, together with its etymology.
Keywords: Лексикография